Multiple toxins and a protease contribute to the aphid‐killing ability of Pseudomonas fluorescens PpR24 - Deepa Paliwal; Mojgan Rabiey; Tim H. Mauchline; Keywan Hassani‐Pak; Ralf Nauen; Carol Wagstaff; Simon Andrews; Chris Bass; Robert W. Jackson (Environmental Microbiology, 2024)
Aphids are globally important pests causing damage to a broad range of crops. Due to insecticide resistance, there is an urgent need to develop alternative control strategies. In our previous work, we found Pseudomonas fluorescens PpR24 can orally infect and kill the insecticide‐resistant green‐peach aphid ( Myzus persicae ). However, the genetic basis of the insecticidal capability of PpR24 remains unclear. Genome sequencing of PpR24 confirmed the presence of various insecticidal toxins such as Tc (toxin complexes), Rhs (rearrangement hotspot) elements, and other insect‐killing proteases. Upon aphids infection with PpR24, RNA‐Seq analysis revealed 193 aphid genes were differentially expressed with down‐regulation of 16 detoxification genes. In addition, 1325 PpR24 genes (542 were upregulated and 783 downregulated) were subject to differential expression, including genes responsible for secondary metabolite biosynthesis, the iron‐restriction response, oxidative stress resistance, and virulence factors. Single and double deletion of candidate virulence genes encoding a secreted protease (AprX) and four toxin components (two TcA‐like; one TcB‐like; one TcC‐like insecticidal toxins) showed that all five genes contribute significantly to aphid killing, particularly AprX. This comprehensive host–pathogen transcriptomic analysis provides novel insight into the molecular basis of bacteria‐mediated aphid mortality and the potential of PpR24 as an effective biocontrol agent.

Indole-3-carbinol improves neurobehavioral symptoms in a cerebral ischemic stroke model - Pankaj Paliwal; Gaurav Chauhan; Deepa Gautam; Debabrata Dash; Shashikant C. U. Patne; Sairam Krishnamurthy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)